Freedom Readers. - Looney, Dennis (William and Katherine Devers series in Dante studies, 2011)
Freedom Readers: The African American Reception of Dante Alighieri and the Divine Comedy is a literary-historical study of the many surprising ways in which Dante Alighieri and the Divine Comedy have assumed a position of importance in African American culture. Dennis Looney examines how African American authors have read, interpreted, and responded to Dante and his work from the late 1820s to the present.